Effects of Different Solvents Extractions on Total Polyphenol Content, HPLC Analysis, Antioxidant Capacity, and Antimicrobial Properties of Peppers (Red, Yellow, and Green (Capsicum annum L.)). (19th January 2022) - Mohammad Salamatullah, Ahmad; Hayat, Khizar; Mabood Husain, Fohad; Asif Ahmed, Mohammed; Arzoo, Shaista; Musaad Althbiti, Mohammed; Alzahrani, Abdulhakeem; Al-Zaied, Bandar Ali M.; Kahlil Alyahya, Heba; Albader, Nawal; Nafidi, Hiba-Allah; Bourhia, Mohammed
Abstract : Plants possessing various bioactive compounds and antioxidant components have gained enormous attention because of their efficacy in enhancing human health and nutrition. Peppers ( Capsicum annuum L.), because of their color, flavor, and nutritional value, are considered as one of the most popular vegetables around the world. In the present investigation, the effect of different solvents extractions (methanol, ethanol, and water) and oven drying on the antioxidant and antimicrobial properties was studied of red, yellow, and green peppers. The green pepper water extract showed the highest total polyphenol content (30.15 mg GAE/g DW) followed by red pepper water extract (28.73 mg GAE/g DW) and yellow pepper water extract (27.68 mg GAE/g DW), respectively. The methanol extracts of all the pepper samples showed higher TPC as compared to the ethanol extract. A similar trend was observed with the total flavonoid content (TFC). The antioxidant assays (DPPH scavenging and reducing power) echoed the findings of TPC and TFC. In both antioxidant assays, the highest antioxidant activity was shown by the water extract of green pepper, which was followed by the water extract of red pepper and yellow pepper. Furthermore, all extracts were assessed for their potential antimicrobial activity against bacterial and fungal pathogens. Aqueous extracts of all three pepper samples exhibited slightly higher inhibition zones as compared to their corresponding ethanolic and methanolic extract. Minimum inhibitory concentration (MIC) values ranged from 0.5 to 8.0 mg/ml. The lowest MIC values ranging from 0.5 to 2.0 mg/ml concentration were recorded for aqueous extracts of green pepper. High-performance liquid chromatography (HPLC) analysis revealed tannic acid as the major phenolic compound in all three pepper samples. Thus, it is envisaged that the microwave drying/heating technique can improve the antioxidant and antimicrobial activity of the pepper.